P-points, MAD families and cardinal invariants - Guzmán González, Osvaldo (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
The main topics of this thesis are cardinal invariants, P-points and MAD families. We answer several open questions found in the literature. The main original results on this thesis are the following: 1. there is a +-Ramsey MAD family. This answers an old question of Michael Hrušák. 2. There are no P-points in the Silver model, answering a question of Michael Hrušák (this is joint work with David Chodounský). 3. the statement \There are no P-points" is consistent with the continuum being arbitrarily large, this answers an open question regarding P-points (see [68], this is joint work with David Chodounský). 4. A Borel ideal is Shelah-Steprāns if and only if it is Katětov above FINxFIN: This entails that Shelah-Steprāns MAD families have very strong indestructibility properties (This is part of a joint work with Michael Hrušák, Dilip Raghavan and Joerg Brendle). 5. Cohen indestructible MAD families exist generically if and only if b = c (This is part of a joint work with Michael Hrušák, Ariet Ramos and Carlos Martínez). 6. non(M) = !1 implies the (*) principle of Sierpiński. This answers a question of Arnie Miller.

Los principales temas de esta tesis son invariantes cardinales, P-puntos y familias MAD. Respondemos a varias preguntas abiertas encontradas en la literatura. Los principales resultados originales de esta tesis son los siguientes: 1. Hay una familia MAD que es +-Ramsey. Esto responde a una vieja pregunta de Michael Hrušák. 2. No hay P-puntos en el modelo de Silver, respondiendo a una pregunta de Michael Michael Hrušák (esto es trabajo conjunto con David Chodounský). 3. La afirmación "No hay P-puntos" es consistente con que el continuo sea arbitrariamente grande, esto responde a una pregunta abierta con respecto a P-puntos, esto es trabajo conjunto con David Chodounský. 4. Un ideal Boreliano es Shelah-Steprāns si y sólo si esta Katětov arriba de FINxFIN. Esto implica que las familias Shelah-Steprāns MAD tienen propiedades de indestructibilidad muy fuertes (Esto es parte de un trabajo conjunto con Michael Hrušák, Dilip Raghavan y Joerg Brendle). 5. Familias MAD Cohen indestructible existen genéricamente si y sólo si b = c (Esto es parte de un trabajo conjunto con Michael Hrušák, Ariet Ramos y Carlos Martínez). 6. non(M) = !1 implica el principio (*) de Sierpiński. Esto responde a una pregunta de Arnie Miller.
Instituto de Física y Matemáticas. Facultad de Ciencias Físico Matemáticas. Unidad Morelia del Instituto de Matemáticas de la UNAM. Posgrado Conjunto de Doctorado en Ciencias Matemáticas
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2239; info:eu-repo/classification/cti/1; IFM-D-2017-1206; Ideales Shelah-Steprāns; P-puntos; Principio de Sierpiński